Efek Ekstrak Teh Rosella Merah (Hibiscus sabdariffa Linn)terhadap Penghambatan Aktifasi NF-KB, Ekspresi Protein TNF-a dan ICAM-1pada Biakan HUVECS yang Dipapar dengan Low Density Lipoprotein Teroksidasi - Dwi Sarbini; Djanggan Sargowo; M Saifur Rohman (Jurnal Kardiologi Indonesia, 2007)
Background. Atherosclerosis disease has been a global threat. Ox-LDL was one of major source of atherogenesis process, through the ROS formation which would then activate NF-KB and increase the expression of TNF-a and ICAM-1, leading to the occurrence of inflammation. Recent studies indicate that red Rosella tea is a tropical plant containing antioxidant (protocatechuic acid and antocyanin) and ascorbate acid. This tea is widely distributed in Indonesia. The mechanism of action of this tea on the inhibition of atherogenesis has not been largely known. This study aim to investigate the effect and mechanism of the red Rosella tea on the expression of NF-KB, TNF-aand ICAM-1.Methods and results.Cultured endothelial cell, HUVECs (Human Umbilical Vein Endothelial), is used for a model of endothelial cells. There are 5 groups: 1) HUVECs culture without Ox-LDL as negative control; 2) HUVECs culture with Ox-LDL as positive control; and 3 groups given various dosages of the red Rosella tea (0.001 mg/ml, 0.005 mg/ml and 0.01 mg/ml) and Ox-LDL. OxLDL (40 mg/ml) is added on HUVECs to stimulate responds of endothelial cells mimicking dyslipidemia condition. The Red Rosella tea were given 2 h before Ox-LDL treatment. The NF-KB activaton, the protein expressions of TNF-aand ICAM-1 are detected by immunohistochemistry.Treatment with red rosella tea on Ox-LDL-treated HUVECs resulted in prevention of NF-KB activation which in turn inhibited the increased of TNF-aand ICAM-1 protein expressions. Spearman‘s correlation analysis showed that there is negative correlations between dosages of red tea with NF-KB activation, TNF-aand ICAM-1 protein expressions (p=0.01, Correlation Coeff= -1).Conclusions. This study indicates the benefit of red Rosella tea on the prevention and medication for atherosclerosis disease.